2021
DOI: 10.1111/ijcp.15006
|View full text |Cite
|
Sign up to set email alerts
|

Association between different systemic therapies and the risk of tuberculosis in psoriasis patients: A population‐based study

Abstract: Tuberculosis (TB) contributes to a major public health issue worldwide, and its risk increases when the host immune system is impaired. This could be attributed to an underlying chronic disease, an immunologic disorder or use of immunosuppressants. [1][2][3][4][5] Psoriasis is a chronic inflammatory skin disorder that involves a complex interplay of cytokines, immune cells and the cutaneous tissue. In addition to newer biologic agents that target specific molecules in the pathogenesis of psoriasis, the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…With methotrexate, an increased risk of tubercular reactivation is evidenced ( 23 ). The frequent use of this treatment before initiation of biological therapy may cause confusion regarding which drugs cause LTBI reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…With methotrexate, an increased risk of tubercular reactivation is evidenced ( 23 ). The frequent use of this treatment before initiation of biological therapy may cause confusion regarding which drugs cause LTBI reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…FK506, a calcineurin inhibitor, can effectively inhibit the production of IL-2, IL-4, and IL-3; furthermore, it can inhibit the proliferation and the activation of T cells ( 30 ). A prospective cohort study of psoriasis patients in Taiwan showed that patients treated with FK506 had a higher risk of tuberculosis (hazard ratio [HR], 5.31; 95% CI, 1.66 to 17.01) ( 31 ). It is evident that LEF and FK506 will significantly increase the risk of ATB in patients with autoimmune diseases, while they tend to produce negative T-SPOT.TB results.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, it is established that MTX raises the risk of TB [ 18 , 19 , 20 ]. As many of the patients with moderate and severe psoriasis were treated with MTX before starting biological therapy, it cannot be known for sure which of the drugs induced the appearance of LTBI.…”
Section: Discussionmentioning
confidence: 99%